Fluorine and phosphine oxide containing homo and copolyimides - ÇAKMAKÇI, EMRAH (ELSEVIER SCIENCE SA, 2016)
In recent years the synthesis of fluorinated polyimides has become an active area of research. In this study perfluoroallcyl and phosphine oxide containing diamine monomer, bis(3,3'-aminophenyl)(3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl) phosphine oxide (mDA13FAPO), was successfully prepared. mDA13FAPO was reacted with four different commercial dianhydrides (BTDA, PMDA, ODPA and 6FDA) and corresponding homopolyimides were prepared by thermal and solution imidization techniques. However, homopolyimides of mDA13FAPO exhibited poor film forming properties. In order to overcome this problem different amounts of mDA13FAPO containing copolyimides with BTDA and ODA were prepared. The flame retardancy of the copolyimides was examined by limiting oxygen index measurements. The surface energies of the copolyimides were determined by contact angle measurements. mDA13FPO containing homopolyimides exhibited moderate Tg values (194-233 degrees C), good thermal stability and excellent solubility. The presence of ODA greatly improved the film forming properties and crack-free, creasable copolyimide films were obtained. As the amount of mDA13FAPO was increased, the flame retardancy and the water contact angles of the copolyimides increased while the surface energies and the glass transition temperatures decreased. (C) 2016 Published by Elsevier B.V.
Keywords: Fluorine; Phosphine oxide; Polyimides; Surface energy; PHOSPHORUS-CONTAINING POLYIMIDES; GAS PERMEATION PROPERTIES; PHENYLPHOSPHINE OXIDE; FLAME-RETARDANT; SIDE-GROUPS; MEMBRANES; PERVAPORATION; OLIGOMERS; PROPERTY; POLYMERS